Myofibroblasts in hepatitis B related cirrhosis and hepatocellular carcinoma. Issue 5 (May 1992) - Chau, K Y; Lily, M A; Wu, P C; Yau, W L
Abstract : Peritoneal liver biopsy specimens from eight patients with hepatitis B associated cirrhosis, complicated by hepatocellular carcinoma, were studied for identification and localisation of myofibroblasts. The avidin-biotin peroxidase complex technique was used on paraffin wax sections, using monoclonal antibodies for actin and desmin, and ultrastructural examination was performed. Myofibroblasts were found in seven of the eight cirrhotic specimens and in all eight tumour specimens. They were identified in the fibrotic areas by the immunohistochemical technique, but ultrastructural examination disclosed their presence in the perisinusoidal space and between tumour cells.